The Redox State of Iron: A Powerful Indicator of Hydrothermal Alteration - Studemeister, Paul (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1983)
Summary The redox state of iron, (Fe,2/Fe,), in rocks is a useful Indicator of hydrothermal alteration. In general, rocks are resistant to shifts in (Fe,2/Fe,) unless large volumes of fluid or high concentrations of exotic reactants such as H2 or O2 are present. The earth's surface in equilibrium with the atmosphere is an oxidizing environment; surface waters carry in solution O2 plus SO42. Laboratory experiments conducted at high temperatures reveal that water in the presence of ferrous minerals tends to dissociate and yield free hydrogen. At depths exceeding a few kilometres, waters are hot and reducing with H2 H20 = 1 30 to 1/60. In a hydrothermal convection cell, rocks along the descending limbs will be oxidized whereas rocks along the ascending limbs will be reduced by the circulating water.